Correlation Analysis Between Teachers’ Teaching Psychological Behavior and Classroom Development Based on Data Analysis - Fan, Zhongtao; Liu, Jun (Frontiers in Psychology, 2022)
Teachers' teaching psychological behavior and classroom development are the current research hotspots in the field of educational psychology. How to realize the data analysis of teachers' teaching psychological behavior and classroom development is a problem that researchers urgently need to solve. Based on the theory of data correlation analysis, this paper uses modern Internet technology and big data analysis teacher teaching system to quantitatively and qualitatively analyze the potential of students, and build a corresponding model. Through rule correlation technology, the article studies various internal correlations between teachers' teaching psychological behavior, extracts valuable information from various daily data of students through big data analysis technology, and the WEB teacher's teaching psychological behavior analysis system based on B/S structure solves the problem that the traditional model cannot measure. In the simulation process, the system is implemented by MVC three-tier architecture, the database uses MYSQL 5.0, the prediction questionnaire is formulated on the basis of the literature method and interviews, and the scale is compiled and tested after repeated revisions. Project analysis and factor analysis are performed on the data obtained from the table test to construct and screen indicators, The experimental results show that the teacher's classroom teaching behavior index system adopted by the system is practical and feasible, including 3 first-level indicators, 10 second-level indicators and 21 third-level indicators. The system has 87.1% completeness, which effectively improves teachers' teaching psychology.